Modelagem discreta de transição epitelial mesenquimal: o papel da matriz extracelular - Cassol, Luísa Vargas (2024)
The epithelial-mesenchymal transition (EMT) is a biological process in which epithelial cells undergo biochemical changes and are transformed into mesenchymal cells, a transition that plays a crucial role in tumor propagation through metastasis. Several factors contribute to this transition, among them the extracellular matrix (ECM), which, in its healthy state, serves a protective function against tumor development and spread. Long non-coding RNAs (lncRNAs) represent a new category of non-coding RNAs that play a significant role in cancer progression and can also be a corroborating factor for EMT. The advancement in understanding the molecules and interactions governing the complex EMT system has demanded the application of computational approaches revealing the intricacies of its dynamics. Against this backdrop, the present study aims to investigate the dynamics of epithelialmesenchymal transition, considering the influence of new molecules from the extracellular matrix, the behavior of the long non-coding RNA ATB (lncRNA-ATB) in the model, and the temporal evolution of the system, based on a previously proposed breast cancer network. Logical modeling was used for these analyses, and simulations were conducted comparing the atemporal model using the GINsim software to the temporal model employing the Ma- BoSS software simulating time. In the end, the comparison results between the atemporal and temporal models proved to be consistent. Additionally, the combination of the ECM with transforming growth factor-beta (TGF-β) revealed the progression of the transition when the ECM is rigid, while the influence of lncRNA-ATB was associated with a new stable state, indicating its relation to the destabilization of cellular transition.